Case report: Treatment of cyclobenzaprine ingestion in two dogs with intravenous intralipid therapy - Dreese, Kaitlyn; Odunayo, Adesola; Bucknoff, Melissa C. (Frontiers in Veterinary Science, 2024)
Introduction -The objective of this case series is to describe the clinical signs and outcome of cyclobenzaprine ingestion in two dogs treated with intralipid emulsion (ILE) and supportive care.Case or Series Summary -Two dogs presented for evaluation of cyclobenzaprine ingestion. A 4year-old female-spayed Rat Terrier (dog 1) presented within four hours of ingestion of cyclobenzaprine (between 9.7 -25.9 mg/kg). The dog experienced abnormal behavior, agitation, tremors, tachycardia, and hypertension. There were no significant clinicopathological abnormalities. The dog was treated with ILE, cyproheptadine, and activated charcoal. All clinical signs resolved after treatment. A 5-month-old female intact Mixed Breed Dog (dog 2) presented after ingestion of an unknown amount of cyclobenzaprine two to three hours prior to presentation. The dog experienced dull mentation, tremors, loss of gag reflex, tachycardia, and hypertension. There were no significant clinicopathological abnormalities. Orogastric decontamination was performed via gastric lavage and activated charcoal was given via orogastric tube, followed by ILE. All clinical signs resolved after therapeutic intervention.Discussion -This is the first report documenting clinicals signs of cyclobenzaprine toxicity in two dogs followed by successful treatment with gastric emptying, ILE, and supportive care.